Mediating effects of grit and perceived social support between resilience and post-traumatic growth in the emergency room nurses - Min, Eun-Hee; Park, Hyung-Ran (Frontiers in Psychology, 2025)
Emergency room (ER) nurses are frequently exposed to traumatic events, leading to mental fatigue and reduced quality of life. However, to overcome such events, some nurses exhibit positive psychological transformation and behavioural change, known as post-traumatic growth (PTG). This cross-sectional descriptive study examined the mediating effects of grit and perceived social support on the relationship between resilience and PTG among ER nurses. Data were collected from 182 ER nurses across seven general hospitals in Chungcheong Province, South Korea. SPSS version 26.0 and the PROCESS macro program (MODEL 6) were used for data analysis. The results indicated that resilience significantly affected ER nurses' PTG. Furthermore, grit and perceived social support mediated this relationship. The findings emphasise the importance of enhancing resilience, grit, and perceived social support to promote ER nurses' PTG.